The Effectiveness Of Application Of Marketing Strategies In Private Higher Education - Nuriadi, Nuriadi (AKADEMIK: Jurnal Mahasiswa Humanis, 2021)
For private higher education institutions, education is an educational service. Therefore, there needs to be a measurable effort in finding students. One common way of doing this is by implementing a marketing mix. Starting from publications, promotions, and the application of affordable educational costs, as well as various educational facilities. Based on this, this study was conducted to reveal the effectiveness of implementing marketing strategies in private higher education in Banten Province. The strategic step in answering the objectives of this research is to use a qualitative approach and descriptive analysis. The unit of analysis was students, and research data was obtained through a simple random distribution of questionnaires. The results showed that the background/characteristics of the students greatly influenced the marketing strategy model used. Thus, universities need to conduct research on student profiles comprehensively, from demographics to the presence of other universities. The price penetration strategy is the most dominant factor for the urban market, in the lower-middle class category. Thus, the main key in the effectiveness of implementing a private higher education marketing strategy is the affordability of education costs.